The Art Documentary in the Postwar Period - Angela Dalle Vacche (Aniki: Revista Portuguesa da Imagem em Movimento, 2014)
In the wake of the Holocaust and Hiroshima, the exploration of human creativity became central to reestablish the humanity of humankind. By closely following the art documentary, French film critic André Bazin focused on this genre in relation to painting, because the latter was the most elitist of all media. In the case of Alain Resnais’s Van Gogh (1948), Bazin used the encounter of cinema and painting as an example of symbiosis between the objects of still life and the objectifying impact of the camera lens. The critic’s writings on the art documentary also underlined the anti anthropocentric and cosmological vocation of the cinema. By turning the pictorial frame into the screen of cinema, Resnais’s Van Gogh de-centers the viewer into an introspective world of landscapes and rooms, where the painter himself is an absent participant or an anonymous figure rather than a protagonist in control. While self-portraiture in Van Gogh is elusive and Bazin’s scientific metaphors are vitalistic, the depth of human psychology remains as mysterious as the creativity of nature on this earth and the origin of life in the cosmos.